Risk profiles in integrated project delivery agreements - a comparative study - Sajip, Mihika A., author; Mehany, Mohammed S. Hashem M., advisor; Harper, Christofer M., advisor; Switzer, Ralph, Jr., committee member (Colorado State University. Libraries, 2020)
Integrated Project Delivery (IPD) is a collaborative and communicative Project Delivery Method (PDM). It promotes lean principles such as team integration, Last Planner System, Big Room concept, Pull Planning, etc. Another important feature that sets it apart from other Project Delivery Methods is Multi-Party Agreements. Unlike other agreements that only two parties share, multi-party agreements aim to have as many relevant parties as its signing members. Sutter Health's IFOA, ConsensusDocs 300, and AIA agreements for IPD are the most widely used agreements on IPD Projects. There are an enormous number of unknowns to these agreements, as they haven't been as tried and tested in the courts of law as much as other agreements. There is a negligible amount of research done on them. No research exists on the comparison between the content of these agreements. To address this issue and to study and compare their clauses, a combination study involving collecting empirical and theoretical data was initiated. Data was collected through pilot interviews, an electronic survey and a detailed comparative content analysis. The objectives of this study are to provide information on a) Clauses in the agreements that require modification; b) Clauses in the agreements that have come up during disputes c) Similarities and differences in between these clauses; d) Effects of multi-party agreements on contractual privity during disputes; e) Mitigation strategies used to avoid and wade through risks. This research can also be utilized by organizations as an aid while selecting a suitable agreement for their IPD Project.
Keywords: comparative study; contracts; IPD; comparison; agreements; integrated project delivery